Successful treatment of a childhood synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome with subcutaneous methotrexate: A case report - Akçaboy, Meltem; Bakkaloğlu-Ezgü, Sevcan Azime; Büyükkaragöz, Bahar; Isıyel, Emel; Kandur, Yasar; Hasanoğlu, Enver; Buyan, Necla (The Turkish Journal of Pediatrics, 2017)
SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis and osteitis) is defined as a syndrome that is related to various osteoarticular manifestations and chronic dermatological conditions especially severe acne. SAPHO syndrome is a rare and unusual clinical entity in childhood and treatment choices are variable. We report an 11-year-old girl who suffered from SAPHO syndrome and successfully treated with subcutaneous methotrexate. We report our case in order to take attention to this rare clinical condition in evaluating patients and also to point out that treatment options beyond biologic agents should be the first line treatment in childhood.
Keywords: SAPHO syndrome; children; methotrexate; treatment